108k views
5 votes
Given the equation h(z)=2(z-4),find h(-2).

User Tornskaden
by
5.1k points

2 Answers

1 vote
2(z-4)
2(-2-4)
2(-6)
12
User Ptierno
by
5.1k points
5 votes

Answer:


\boxed {\tt h(-2)= -12}

Explanation:

We are given the function:


h(z)=2(z-4)

We want to find h(-2) so we must substitute -2 in for each z.


h(-2)=2(-2-4)

Now, solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, and Subtraction.

Solve inside the parentheses first. Subtract 4 from -2.


h(-2)=2(-6)

Multiply 2 and -6.


h(-2)=-12

For h(z)= 2(z-4), h(-2)= -12

User Prasath S
by
5.4k points